2021
DOI: 10.1177/2050313x211065793
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID-19 infection triggering oral herpes zoster? A case report

Abstract: Patients affected with COVID-19 are at risk of developing serious and life-threatening conditions. The clinical manifestations of COVID-19 were detected in asymptomatic cases to severe clinical symptoms with a major impact on the respiratory system. A few cases of cutaneous as well as an oral lesion of herpes zoster in patients with COVID-19 were reported in the literature. We present a case of the rapid appearance of the oral lesion as a manifestation of herpes zoster associated with COVID-19 infection. Our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Twenty-one case reports and two case series found ulcerative or prodromal erosive lesions (4,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The ulcerations could be single (32.5%) or multiple (67.5%), described as herpetiform, aphthous, hemorrhagic, associated or not with maculo-papular eruptions or erythematous areas.…”
Section: 1/ Ulcerations Ischemia and Necrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one case reports and two case series found ulcerative or prodromal erosive lesions (4,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The ulcerations could be single (32.5%) or multiple (67.5%), described as herpetiform, aphthous, hemorrhagic, associated or not with maculo-papular eruptions or erythematous areas.…”
Section: 1/ Ulcerations Ischemia and Necrosismentioning
confidence: 99%
“…Regarding cheilitis, the literature review found painful cheilitis in four prevalence studies and ten case studies (9,11,(13)(14)(15)(17)(18)(19)21,22,30,35). The prevalence was higher in children.…”
Section: 2/ Hemorrhagic and Inflammatory Lesionsmentioning
confidence: 99%
“…VZV can also be reactivated with symptomatic COVID-19 [29] . The SARS-Cov-2 virus causes immune dysfunction and decreased body resistance to infections, therefore, it may lead to oral HZ [37] . In one study which reported the recurrent oral HZ in two patients with leukemia after COVID-19 infection, one of the patients was treated by a 2-week course of valacyclovir with a steroid taper, and the other patient was treated with acyclovir intravenously, and then converted to oral valacyclovir to complete in a 2-week treatment period, and thereafter received prophylactic dosing of valacyclovir [28] .…”
Section: Oral Herpes Zostermentioning
confidence: 99%
“…In addition to skin diseases in which stress plays an important role, such as psoriasis, alopecia areata and chronic urticaria, an increase in HZ cases admitted to the dermatology clinic has been reported. However, the increase in the frequency of HZ should not be associated only with stress (5). There is even an opinion that argues that the presence of HZ may be a COVID-19 indicator (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in the frequency of HZ should not be associated only with stress (5). There is even an opinion that argues that the presence of HZ may be a COVID-19 indicator (5,6). T cell dysfunction may occur in coronavirus disease, and the patient may develop lymphopenia, increased lymphocyte apoptosis, and impaired lymphopoiesis.…”
Section: Introductionmentioning
confidence: 99%